ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA PT.TAHTA AULIA PERKASA DI SAMARINDA - Putriana, Wida Harry (EKONOMIA, 2014)
Widya harry putriani university economic faculities agustus 17 1945 samarinda.Analisis sources and sources and uses of working capital on PT.Tahta aulia perkasa on samarinda.Â  Under the guidance of the mother and father Elfreda A.Lau and Adi SurosoProblem in this study wether PT.Tahta aulia perkasa mighty throne in samarinda not use the resources effectively according,purpose of this study was to determaine wheter the sources and uses of working capital both short-term and long-term use approiate of time.discuss the source and uses of working capital is a sorce of working capitalof the company is drived datiboperasi depreciation profit fan modal bank loan of Rp.640.612.800,50While is use is to purchase penambahan investemen firm,long-term debt amounted to Rp.350.747.456,50 so that the increase in working capital of the company amonted to Rp.289.856.334,00 in other words,short-term funds have not ben used for short-term as well as long-term funds have not been used for long-term